Improving identification of idiopathic intracranial hypertension patients in Swedish patient register. (28th November 2017) - Sundholm, A.; Burkill, S.; Bahmanyar, S.; Nilsson Remahl, A. I. M.
Abstract : Objective: Idiopathic intracranial hypertension (IIH) is often misdiagnosed. This can cause problems if conducting register‐based studies. The study purpose was to produce algorithms that better identify patients with correct diagnosis of IIH in the Swedish National Patient Register (NPR). Methods: Patients with ICD‐10 code G93.2 for IIH registered in the NPR (2006‐2013, Stockholm County) were included and diagnosis validated by medical record reviews. Patients were randomized into two groups: one used to produce the algorithm (n = 105) and one for validation (n = 102). We tested variables possible to extract from registries and used forward stepwise logistic regression which provided a predicted probability of correct diagnosis for each patient. Results: We included 207 patients of which 135 had confirmed IIH. This gave a positive predictive value of 65.2% (CI: 58.4‐71.4). The algorithm produced with variables extracted from registries, that is, age, number of times with diagnosis code G93.2 recorded (>2 times), and acetazolamide treatment, predicted the diagnosis correctly 88.2% (CI: 80.3‐93.3) of the time. Excluding treatment data from the algorithm did not change the prediction notably, 86.3% (CI: 78.1‐91.7). Conclusion: We produced two algorithms that with improved accuracy predict whether an IIH diagnosis in the NPR is correct. This can be a useful tool when performing register‐based studies.